Antioxidant Effects of Cinnamon Extract on Liver Health in Rats - Al Darraji Raad Kareem Alwan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Cinnamon is medical palnt a spice derived from the Cinnamomum genus and it is renowned for its unique flavor, aroma and potential health-profits, mainly its antioxidant properties. This study aim to evaluating the protective effects of cinnamon-extract on liver damage induced by Thioacetamide (TAA) in rats. Thirty adult male Wistar-rats were distributed into three groups: a Negative Control (NG) group, Positive Control (PG) group that treated with TAA to induce liver injury, and Treated Group (TG) that received both TAA and cinnamon extract (50-100 mg/kg body weight daily) for one month. Liver functions were assessed by measuring Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and alkaline phosphatase (ALP) enzyme levels. The results shown a significant increasing in ALT and AST levels in the PG group compared to the NG group, indicating liver damage. The treated group of rats showed a reduction in ALT and AST levels compared to the positive control group although the decrease was not statistically significant where as Alkaline phosphatase in positive control group exhibited a significant elevation while the treated group showed a non-significant decrease. These results showed that cinnamon extract might offer fractional protection against liver damage induced by TAA due to its antioxidant role that reduce oxidative stress in the liver.